Low dose desensitisation does not reduce the toxicity of sulphasalazine in rheumatoid arthritis. Issue 5 (May 1996) - McInnes, I B; Porter, D; Murphy, E A; Thomson, E A; Madhok, R; Hunter, J A; Pullar, T; Capell, H A
Abstract : OBJECTIVE: To examine the proposal that pretreatment low dose desensitisation may reduce the incidence of toxicity of sulphasalazine in the treatment of rheumatoid arthritis (RA). METHODS: A double blind, placebo controlled trial was performed with 422 patients satisfying the American College of Rheumatology criteria for RA who required sulphasalazine treatment because of increased disease activity. Patients received either sulphasalazine desensitisation, or placebo, for three weeks before commencement of sulphasalazine treatment. The frequency and nature of adverse effects and changes in clinical and laboratory parameters of disease activity were measured after three and six months. RESULTS: Improvement in the efficacy of sulphalasazine (measured by clinical and laboratory parameters) was significant and similar in magnitude in both groups. There was no significant difference between actively and placebo desensitised patients as regards the incidence or profile of adverse effects (toxicity). CONCLUSION: Pretreatment low dose desensitisation is unhelpful in reducing the toxicity associated with sulphasalazine treatment of RA.